Glyceraldehyde-3-Phosphate Dehydrogenase of Babesia microti Is a Plasminogen- and Actin-Binding Protein - Liu, Xiangye; Li, Huiqin; Deng, Hongkuan; Zheng, Chen; Yan, Hongru; Chen, Zetian; Bian, Anning; Chen, Jiaxu; Zheng, Kuiyang (Frontiers in Veterinary Science, 2019)
Babesia microti, an intraerythrocytic protozoa, can cause an emerging tick-borne disease—Human babesiosis. The parasite can successfully invade host red blood cells owing to the assistance of molecules expressed by babesia. GAPDH, the housekeeping intracellular glycolytic enzyme, can also be expressed in the external of cells, where contributes to binding to several molecules such as plasminogen and actin. In the present study, we identified B. microti GAPDH (BmGAPDH) and generated the recombinant BmGAPDH (rBmGAPDH) via an E. coli expression system. Furthermore, we confirmed its catalytic dehydration activity in vitro. Moreover, we also demonstrated that rBmGAPDH could bind to human plasminogen and mouse α-actin. In addition, we demonstrated that rBmGAPDH could recognize anti-B. microti mouse serum. In conclusion, BmGAPDH is a multifunctional glycolytic enzyme, which can bind to host plasminogen and α-actin.